Herbert C. Kelman and Peace Psychology - Arias Gallegos, Walter Lizandro; Klappenbach, Hugo; Ardila, Rubén; López-López, Wilson; Caycho-Rodríguez, Tomás (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2023)
This article reviews the life and work of Herbert Kelman (1927-2022), one of the most influential social psychologists of the 20th century and of the present century. His theories have had a favorable impact on the resolution of international conflicts, based on experimental evidence and his intervention in various international events in the Middle East and other parts of the world. In addition, he was one of the leading promoters of the psychology of peace and published a wide variety of a well-received articles, book chapters, and books in the field of social psychology. He also was president of the Interamerican Society of Psychology (ISP) between 1976 and 1979, with a display of functions that are the object of our analysis. For all these reasons, Kelman is an author, whose work deserves to be reviewed and analyzed on the occasion of his recent death, to give continuity to his ideas and his contributions in the field of conflict resolution.